A Small Essay About a Big Boulevard - Grigoryeva, Elena (project baikal, 2015)
The essay presents the analogies of turning city borders and walls into boulevards and gardens through the examples of Moscow and Irkutsk. The main street of Irkutsk is viewed in a new light, as a boulevard. It is proposed to take into consideration the peculiarities of the four sense-parts of the street when working on design codes.